Solving the mystery: Hyalinized cyst wall containing organism‐like structures in a lung transplant donor. Issue 5 (22nd June 2018) - Bini Viotti, Julia; Loebe, Matthias; Brozzi, Nicolas; Pinto, Andre; Simkins, Jacques; Cloke, Christina M.; Camargo, Jose F.; Salama, Sam; Abbo, Lilian M.
Abstract: A 59‐year‐old man with non‐ischemic cardiomyopathy underwent orthotopic heart transplantation. The donor, a 31‐year‐old male declared brain dead after a gunshot wound to the head, was considered high risk due to history of incarceration, illicit drug use, and sex with a HIV‐positive partner. At organ procurement, the heart, kidneys, pancreas, and liver looked grossly normal. A small right lower lobe nodule was noticed, and lung biopsy was performed. Bronchoscopy showed purulent secretions in the right lower lobe. Images from pathology are presented. Lung biopsy confirmed the presence of hyalinized cyst wall containing organism‐like structures. A combination of culture, microscopic morphology, and gene sequencing was used to identify the causative organism. The patient and all other organ recipients received appropriate antifungal prophylaxis and remain asymptomatic 6 months post‐transplant.